A Critical Review on Evaluating Integrated Pest Management in Agricultural Systems: Progress and Prospects - Chiranjeev Lairikyengbam; Nikam Jaiswal; Bhawna Bamnia; Munish Kaundal (Archives of Current Research International, 2025)
Integrated Pest Management (IPM) is a cornerstone of sustainable agriculture. IPM is an ecological approach to managing pest populations. It emphasizes the use of multiple tactics to suppress pests while minimizing negative impacts on the environment and human health. In contrast to traditional practices that focus solely on eradication through pesticides, IPM prioritizes preventative measures, monitoring pest populations, and utilizing biological controls when necessary. This review examines the effectiveness of IPM in addressing contemporary agricultural challenges and analyses its strengths, including its ecological benefits and potential for yield protection. However, it also critically evaluates the limitations of IPM, particularly its dependence on robust monitoring and knowledge-intensive practices.